اثر اعادة هندسة الاعمــــــال في تحقيق المرونة التنظيــــمــــــــــــية لدى عينة من المؤسسات الصناعية النشطة بولاية سوق اهراس - بوفاس الشريف; بوخضرة مريم (My University, 2020)
تسلط الدراسة الضوء على مدى تأثير اعادة هندسة الاعمال كأسلوب من اساليب التغيير التنظيمي بمختلف ابعادها (التنظيمي والبشري ،الاجرائي والتكنولوجي ) في تحقيق المرونة التنظيمية لدى عينة من المؤسسات الصناعية بولاية سوق اهراس، ومن اجل القيام بالدراسة تم الاستعانة بالمنهج الوصفي التحليلي، وكذا منهج دراسة الحالة من خلال التطرق الى عينة من المؤسسات الصناعية بولاية سوق اهراس تنشط في قطاعات مختلفة وتم استخدام الاستبانة كأداة للتحليل والاستعانة بالبرنامج الاحصائيSPSS وجملة من الاختبارات الاحصائية ، وتوصلت الدراسة الى جملة من النتائج مفادها وجود تأثير ايجابي لإعادة هندسة الاعمال في اكتساب المرونة التنظيمية للمؤسسات المعنية بالدراسة ودعم قدرتها على الاستجابة للتغيرات والتطورات التي تفرضها بيئة الاعمال وظروف المنافسة . The study sheds light on the impact of business re-engineering as a method of organizational change in its various dimensions (organizational, human, procedural and technological) in achieving organizational flexibility among a sample of industrial institutions in the state of Souk Ahras In order to carry out the study, the analytical descriptive approach was used, As well as the case study approach by referring to a sample of industrial establishments in the state of Souk Ahras that are active in different sectors. The questionnaire was used as a tool for analysis and the use of the SPSS statistical program and a set of statistical tests The study found out a number of results including that there is a positive effect of the re-engineering business in the acquisition of organizational flexibility for institutions involved in the study and support its ability to respond to changes and developments and business conditions imposed by the competition environment.